HYDROGEN FROM COAL GASIFICATION: AN ECONOMICAL PATHWAY TO A SUSTAINABLE ENERGY FUTURE - Stiegel G.J.; Ramezan M. (My University, 2006)
Although hydrogen is the most abundant element in the universe, it does not occur naturally in large quantities or high concentrations on Earth. Hydrogen must be produced from other compounds such as fossil fuels, biomass, or water and is therefore considered an energy carrier like electricity. Gasification of carbonaceous, hydrogen-containing fuels is an effective method of thermal hydrogen production and is considered to be a key technology in the transition to a hydrogen economy. However, for gasification to play a major role during the transition period, capital and operating cost must be reduced and reliability and performance must be improved. Analyses show that hydrogen produced from coal-based gasification can be competitive with production from natural gas provided the cost of natural gas remains above $4/106 Btu and the high reliability of gasification-based processes can be demonstrated. But for coal to be considered in a carbon-constrained environment, the cost of natural gas would have to be greater than $5.50/106 Btu. The development of advanced technologies, however, offers the potential for significant reductions in capital costs, improved thermal efficiencies, and increased reliability. If these advanced technologies are capable of achieving their goals, the cost of producing hydrogen from coal could be reduced by 25-50%, even with the capture and sequestration of CO2. With these reductions, the cost of natural gas would have to be less than $2.50/106 Btu to compete, a scenario that is very unlikely to occur in the future. This potential cost reduction provides considerable impetus for continuing research and development in the production of hydrogen from coal. © 2005 Elsevier B.V. All rights reserved.
Keywords: COAL; ECONOMICS; GASIFICATION; HYDROGEN